2021
DOI: 10.1097/qad.0000000000002876
|View full text |Cite
|
Sign up to set email alerts
|

Racial, ethnic, and gender disparities in hospitalizations among persons with HIV in the United States and Canada, 2005–2015

Abstract: To examine recent trends and differences in all-cause and cause-specific hospitalization rates by race, ethnicity, and gender among persons with HIV (PWH) in the United States and Canada.Design: HIV clinical cohort consortium. Methods:We followed PWH at least 18 years old in care 2005-2015 in six clinical cohorts. We used modified Clinical Classifications Software to categorize hospital discharge diagnoses. Incidence rate ratios (IRR) were estimated using Poisson regression with robust variances to compare rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The lowest hospitalization rates due to CVD have been observed in Asian men living with HIV. Compared to Black men living with HIV, Asians had a three-fold lower rate of hospitalization due to cardiovascular reasons [32]. Those inequalities may result from a lesser number of CVD risk factors among Asians.…”
Section: Racementioning
confidence: 92%
“…The lowest hospitalization rates due to CVD have been observed in Asian men living with HIV. Compared to Black men living with HIV, Asians had a three-fold lower rate of hospitalization due to cardiovascular reasons [32]. Those inequalities may result from a lesser number of CVD risk factors among Asians.…”
Section: Racementioning
confidence: 92%
“…32 A separate investigation indicated that among cisgender PLWH, Black patients exhibit higher incident rate ratios of cardiovascular hospitalizations compared with similarly aged White patients, irrespective of biological sex. 26 No cardiovascular hospitalization disparities were detected in comparisons of cisgender females to cisgender males or in transgender patients to cisgender male patients. However, additional studies are necessary to better understand the epidemiology of CVD among PLWH by combinations of race/ethnicity, sex, and sexual orientation.…”
Section: Epidemiology Of Hiv and Cardiovascular Diseasementioning
confidence: 93%
“…24 Therefore, given the proportion of PLWH in advanced age has increased over time, it is not surprising that PLWH are increasingly 25 developing chronic comorbid conditions associated with aging, including CVD. 7,26 However, there are disparities in individuals in marginalized identities, such that they experience more aggressive accelerated cardiovascular aging.…”
Section: Epidemiology Of Hiv and Cardiovascular Diseasementioning
confidence: 99%